O movimento de luta por moradia no bairro Capitão Eduardo: processos educativos resgatados pelas lembranças dos seus primeiros moradores - Miriam Regina de Sousa Bezerra (2006)
This is a research on the studies of social movements and education. Its main objective is the comprehension of educational processes lived by the first inhabitants of Capitão Eduardo neighborhood, through their memories of their participation in the homeless movement (MOVIMENTO dos SEM CASA), in the 1980s in Belo Horizonte. It is also about the qualitative research developed by an oral history methodology. Interviews were done with six inhabitants, men and women, black and white, leaders and participants of the movement in the 1980´s. These narratives reveal several educational dimensions experienced by the subjects throughout their lives and apprehended within a specific context from the movement, such as their relationship, their political organization, negotiation skills in struggling situations, and the learning to fight for their rights. Besides these dimensions the school is also spotted as an important space for development. Remembering and articulating these memories with the present time scholastics knowledge and life knowledge built through political struggle are seen by the interviewees as complementary.